Postsynthetic modification of single Pd sites into uncoordinated polypyridine groups of a MOF as the highly efficient catalyst for Heck and Suzuki reactions. (8th May 2018) - Dong, Dapeng; Li, Zhenghua; Liu, Dedi; Yu, Naisen; Zhao, Haiyan; Chen, Huiying; Liu, Jia; Liu, Dongping
Abstract : A novel Pd-HoMOF catalyst was prepared, which displayed good thermal stability and high activity in Heck and Suzuki cross-coupling reactions. Abstract : A novel holmium(iii ) metal–organic framework (Ho-MOF), namely, [Ho(2-TriPP-COO)3 ] (2 ) has been hydrothermally obtained using 4′-(4-carboxyphenyl)-2, 2′:6′, 2′′-terpyridine (2-TriPP-COOH) and Ho(NO3 )3 ·5H2 O, and it is structurally characterized by single-crystal XRD, powder XRD as well as elemental analysis. The postsynthetic modification of Ho-MOF is based on the utilization of a strong coordination effect between Pd 2+ ions and free polypyridine groups in the skeleton of Ho-MOF, which play a critical role to access the highly efficient Pd-HoMOF catalyst. Also, Pd-HoMOF exhibits very high activity in Heck and Suzuki–Miyaura cross-coupling reactions. Moreover, the MOF catalyst displays good thermal stability (up to 400 °C), and it can be recovered and reused for five reaction cycles. The bridging between the MOF structure and homogeneous molecular Pd catalyst represents a good example in designing highly efficient catalysts for various fine chemical transformations.